2021
DOI: 10.1016/j.acra.2020.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Engagement and Educational Value of a Remote Clinical Radiology Learning Environment: Creation of Virtual Read-Out Sessions in Response to the COVID-19 Pandemic

Abstract: Rationale and Objectives: The need for social distancing has resulted in rapid restructuring of medical student education in radiology. While students traditionally spend time learning in the reading room, remote clinical learning requires material shared without direct teaching at the radiology workstation. Can remote clinical learning meet or exceed the educational value of the traditional in-person learning experience? Can student engagement be matched or exceeded in a remote learning environment? Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 7 publications
1
31
0
1
Order By: Relevance
“…About 23% of the respondents in our DFP survey needed to watch some kind of tutorial for use of one or the other digital platform. As reported by other studies, although some programs may require time to get adjusted, we observed that the learning curve was quick for the DFP as witnessed by the lack of difficulties in later meetings [24,25]. Regarding multiinstitutional research among different authors, there may still be issues with all readers getting together at the same time for consensus studies, and may need lot of co-ordination.…”
Section: Limitationssupporting
confidence: 55%
“…About 23% of the respondents in our DFP survey needed to watch some kind of tutorial for use of one or the other digital platform. As reported by other studies, although some programs may require time to get adjusted, we observed that the learning curve was quick for the DFP as witnessed by the lack of difficulties in later meetings [24,25]. Regarding multiinstitutional research among different authors, there may still be issues with all readers getting together at the same time for consensus studies, and may need lot of co-ordination.…”
Section: Limitationssupporting
confidence: 55%
“…The 16 papers used a variety of methodologies, including one cross-sectional study, two quantitative descriptive studies, two quasi-experimental studies, one prospective cohort study and the rest of the ten mixed-method studies. The publications were devoted to exploring the different modalities of digital education, including virtual reality-based simulation training (3 studies) ( De Ponti et al, 2020 ; Kang et al, 2020 ; Weston and Zauche, 2020 ), teleconsultation and virtual rounds (3 studies) ( Bala et al, 2021 ; Sukumar et al, 2021 ; Weber et al, 2021 ), web-based specialized skills learning (2 studies) ( Alpert et al, 2020 ; Shahrjerdi et al, 2020 ), and multimodal online curriculums (8 studies) ( Coffey et al, 2020 ; He et al, 2021 ; Kaliyadan et al, 2020 ; Kasai et al, 2021 ; Michener et al, 2020 ; Samueli et al, 2020 ; Williams et al, 2021 ; Zhou et al, 2020 ). Study outcomes were measured utilizing a series of homemade tools.…”
Section: Resultsmentioning
confidence: 99%
“…Methodological quality, as appraised by the MMAT exercise for the included 16 articles, ranged from 25% to 100%, with one study rated at 100% ( Kang et al, 2020 ); two studies rated at 75% ( Alpert et al, 2020 ; Weston and Zauche, 2020 ); five studied rated at 50% ( Coffey et al, 2020 ; He et al, 2021 ; Kasai et al, 2021 ; Shahrjerdi et al, 2020 ; Zhou et al, 2020 ), and the remaining eight studies rated at 25% ( Bala et al, 2021 ; De Ponti et al, 2020 ; Kaliyadan et al, 2020 ; Michener et al, 2020 ; Samueli et al, 2020 ; Sukumar et al, 2021 ; Weber et al, 2021 ; Williams et al, 2021 ) ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations